LEARNING FROM THE KNOWLEDGE AND EXPERTISE OF OTHERS - Marzano, Gilberto; Ochoa-Siguencia, Luis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
There is a broad consensus that the digital revolution is moving towards the reshaping of traditional professions and jobs. The key idea emerging from expert opinion is that continuing education and learning are essential to help people stay employable in the labor force, and this idea is behind most of the programs and projects co-funded by the European Union over the last decade. Experts are also persuaded that education systems should be adapted to prepare individuals for the changing labor market, and that technological advances will offer new widely available ways to access education.  From this perspective, new forms of learning that harness digital technology should be explored.Recently, we have been seeing an increasing interest from researchers in the engagement of connected people in initiatives and processes with social relevance, such as crowdfunding, crowdsourcing, and crowd sensing.  Crowd learning is a new topic whose borders are not still well-defined.This paper focuses on internet social learning and crowd learning, which appear to be closely related to two new topical fields of investigation: ubiquitous learning and smart and connected cities. It will present some preliminary results from an ongoing research on how interconnected citizen can use, share, remix, and co-construct learning and cultural resources.